Probing interplay of topological properties and electron correlation in TaIrTe4 via nonlinear Hall effect - Haotian Jiang; Tairan Xi; Jiangxu Li; Yangchen He; Hongrui Ma; Yulu Mao; Takashi Taniguchi; Kenji Watanabe; Daniel A. Rhodes; Yang Zhang; Jun Xiao; Ying Wang (Nature Communications)
Abstract Studying the interplay of electron correlation and topology is crucial for discovering new quantum states, such as the fractional quantum spin Hall effect and topological superconductors. Unlike linear transport, nonlinear electrical responses, which encode both symmetry and topological features remain largely unexplored in systems with electron correlation and topology. Here we report that nonlinear Hall measurements reveal the emergence of a correlated state in few-layer topological semimetal TaIrTe₄ below a critical temperature and bias current. This state, exhibiting ultra large nonlinear conductivity, is attributed to the formation of a charge density wave in TaIrTe4 that leads to substantial Berry curvature redistribution. This origin is further supported by the observation of a Raman amplitude mode associated with the charge density wave, enhanced second harmonic generation, and first-principles calculations. Our findings demonstrate that nonlinear electrical probes can access rich phase diagrams in topological materials and highlight the potential of correlated topological systems for developing nonlinear electronics.